KAJIAN JENIS KHAT, MEDIA DAN WARNA KALIGRAFI ARAB DI MASJID KERAMAT DESA PULAU TENGAH KABUPATEN KERINCI PROVINSI JAMBI - Drs. Efrizal, M.Pd., ARYA SADEWA, Drs. Syafei, M.Ag., (Serupa The Journal of Art Education, 2018)
This study aims to describe. Khat 1), Media 2), and Color 3) Arabic calligraphy at the Sacred Mosque, to be known to the people especially the villages of Central Island of Kerinci Regency of Jambi Province. The research method used is qualitative method with descriptive approach. Research location in Central Island village, Kerinci, Jambi. Research subjects are mosque officials, community leaders and artists. Sources of data were obtained from the informants of the Keramat mosque in the form of written notes, audio recordings, videos, photographs, and literature studies. Data were analyzed by qualitative analysis.The result of the research shows that Khat type: Tsuluth and Naskhi. Media: Canvas, Triplek, Cement, Watercolors and Oil Paints Manufacturers, and Colors: Red, Blue, Green, Purple, Pink, Cream, Chocolate, White and Black.Keywords: Khat Type, Media And Color Arabic Calligraphy Mosque Keramat Central Island Village, Kerinci Regency, Jambi Province.